Generation of value in private higher education: an analysis of institutional development plan (IDP) - Silva, Claudio Marcos Maciel da; Rezende, José Francisco de Carvalho (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The purpose of this research is to verify the possibility of establishing a hierarchy of value creation for higher education institutions (HEIs) based on the so-called drivers of intellectual and financial capital informed on the institutional development plans (IDPs) of different private HEIs. For this, it was necessary to identify the elements belonging to the intellectual and financial capital on the IDPs of different HEIs. We analyzed 24 IDPs belonging to the main private HEIs located in Rio de Janeiro state. The results point to a predominance of drivers such as academic degree and work regime, infrastructure, socio-environmental responsibility, revenue and budget.